Evaluation of Retinal Changes in Women with Different Phenotypes of Polycystic Ovary Syndrome - Fatma Sumer; Beril Gurlek; Elif Yildiz; Feyzahan Uzun; Sabri Colak; Ilknur Merve Ayazoglu (Diagnostics)
Background: The aim of our study was to evaluate the retinal nerve fiber layer (RNFL) and macular and choroidal thicknesses in women with different phenotypes of polycystic ovary syndrome (PCOS), and compare these measurements with those of healthy women of reproductive age. Materials and Methods: This prospective case–control study included 120 eyes of 120 women with PCOS, with each of the four distinct phenotypes comprising 30 eyes of 30 women. Additionally, 30 eyes from 30 healthy women were included in the control group. All participants underwent comprehensive ophthalmologic examinations, and RNFL thickness, macular thickness (MT), and choroidal thickness (CT) in each eye were measured via spectral-domain optical coherence tomography. The body mass index (BMI) of the patients was recorded and compared with the retinal changes. Results: The average mean and nasal segments of the RNFL were significantly greater in the PCOS group than in the healthy control group (p < 0.001). There was a statistically significant difference in foveal retinal thickness between the groups (p < 0.001). Our study revealed significant choroidal tissue thickening subfoveally and at locations 500 μm temporal, 500 μm nasal, 1500 μm nasal, and 1500 μm temporal to the fovea in all phenotypes of the PCOS group (p < 0.001). Additionally, there was a positive correlation between BMI and all CT changes. Conclusions: Our findings indicate that the retinal layers and choroid are affected by all phenotypes of PCOS, one of the most common reproductive abnormalities, albeit to varying degrees. Furthermore, these changes were found to be correlated with BMI.